The Effect Of Organic Fertilizer And Nitrogen On Growth And Yield Of Pakchoy (Brassica rapa L. var chinensis) - Beti Mutiara Ramadhani; Koesriharti Koesriharti (PLANTROPICA: Journal of Agricultural Science, 2022)
Pakchoy (Brassica rapa L. var chinensis) is a horticultural plant that has a high economical value and profitable because it is much favored by the community. The use of organic fertilizer is a step to reduce the use of inorganic fertilizer. Nitrogen plays a role in the formation of chlorophyll, proteins, fats, and other organic compounds. The purpose of the study is to study interactions on organic fertilizer and Nitrogen to the growth and yield of pakchoy crops (Brassica rapa L. var chinensis), as well as obtain appropriate dosages on organic fertilizer and Nitrogen on growth and Yield of Pakchoy crops (Brassica rapa L. var chinensis). The research has been conducted in Ampeldento Village, Karangploso Sub-district, Malang District, East Java. The research was held in 24 July – 29 August 2020. The research was used the method of Randomized Block Design Factorial with two factors and 3 replication. The data obtained were analyzed using ANOVA, if there are any real influence then continued with further test LSD 5%. The results showed that there is an interaction between organic fertilizer and nitrogen to the growth and yield, and Obtained doses of organic fertilizer and nitrogen in cow manure 20 tons ha-1 + (1 liter of cow biourine + 10 liters of water) and 130 kg N ha-1 can increase N in the soil so that it can increase the growth and yield of pakchoy plants.